Busana Kontemporer Terispirasi dari Kostum Bajak Laut Jack Sparrow - Tari Susanti; Fendi Nofrian; Desra Imelda; Mirda Aryadi (INDO PUBLISHING, 2026)
The creation of the work entitled “Contemporary Fashion Inspired by Jack Sparrow’s Costume in the Film Pirates of the Caribbean” is motivated by the creator’s interest in the character of Jack Sparrow, who is known for his eccentric, free-spirited, and distinctive fashion style. This project aims to create, realize, and present contemporary fashion designs inspired by Jack Sparrow’s costume through a modern fashion interpretation. The creative method employed consists of three stages: exploration, design, and realization. The exploration stage was conducted through observations of Jack Sparrow’s character and literature studies related to contemporary fashion. The design stage included moodboard development, alternative design creation, design selection, and final design development. The realization stage involved the application of macramé techniques, asymmetric forms, and the use of songket fabric as a supporting material. The resulting works consist of three fashion categories: Ready-to-Wear, Ready-to-Wear Deluxe, and Haute Couture. The results demonstrate that Jack Sparrow’s costume can be transformed into contemporary fashion without losing its visual identity, resulting in designs that possess aesthetic value, strong character, and relevance to current fashion developments.